An Evaluation of Norspermidine on Anti-fungal Effect on Mature Candida albicans Biofilms and Angiogenesis Potential of Dental Pulp Stem Cells - He, Yan; Cao, Yanfan; Xiang, Yangfan; Hu, Fengting; Tang, Fengyu; Zhang, Yanni; Albashari, Abdullkhaleg Ali; Xing, Zhenjie; Luo, Lihua; Sun, Yan; Huang, Qiang; Ye, Qingsong; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Candida albicans (C. albicans) is a common opportunistic pathogen in oral cavity of human beings. Fungal attachment to the biofilm surface is considered to be an important feature of the survival of this fungus which may cause failure in dental function restoration under certain circumstances. Norspermidine (Nspd) is a kind of polyamine molecule, which is common in eukaryotes and prokaryotes. And reported as a potential anti-biofilms agent of bacteria, but its anti-fungal effect remains unclear. To study the effect of Nspd on pre-formed Candida albicans biofilms and co-culture with dental pulp stem cells (DPSCs) to confirm the cytotoxicity of Nspd. Crystal violet assay and colony-forming unit were conducted to monitor the biofilm biomass. XTT assay were used to detect the metabolic activity while live/dead staining were handled to examine fungal viability. Scanning electron microscope imaging was managed to observe biomass and fungal morphology. Real-time quantitative PCR was conducted to study virulence associated gene expression. Through MTT assay, live/dead staining and vascular differentiation assay to detect proliferation and differentiation of DPSCs which was co-cultured with various dosages of Nspd. We found that Nspd could partly inhibit pre-formed C. albicans biofilms including biomass, metabolic activity and fungal viability. Moreover, we observed that Nspd could restrain production of hyphae form to some extent and depressed expression of virulence related genes in C. albicans biofilms. MTT assay and live/dead staining were indicated that DPSCs could proliferated normally with the presence of Nspd. Vascular differentiation assay showed that the presence of Nspd did not significantly affect differentiation of DPSCs. Our study indicated Nspd could inhibit pre-formed C. albicans biofilms effectively, and could not affect proliferation and angiogenetic differentiation of DPSCs under a certain concentration of Nspd. It is a potential novel anti-fungal agent against problems caused by C. albicans biofilms in regenerative dentistry.